2003
DOI: 10.1258/095646203762869151
|View full text |Cite
|
Sign up to set email alerts
|

Let it be sexual: how health care transmission of AIDS in Africa was ignored

Abstract: The consensus among influential AIDS experts that heterosexual transmission accounts for 90% of HIV infections in African adults emerged no later than 1988. We examine evidence available through 1988, including risk measures associating HIV with sexual behaviour, health care, and socioeconomic variables, HIV in children, and risks for HIV in prostitutes and STD patients. Evidence permits the interpretation that health care exposures caused more HIV than sexual transmission. In general population studies, crude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 66 publications
1
63
0
1
Order By: Relevance
“…Incorporating data on medical transmission into the model in this paper would likely further improve its predictive power in analyzing the determinants of HIV spread (Drucker et al, 2001;Potterat et al, 2002;Gisselquist et al, 2003;Brewer et al 2003;Brody, 2004;Deuchert andBrody 2006, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating data on medical transmission into the model in this paper would likely further improve its predictive power in analyzing the determinants of HIV spread (Drucker et al, 2001;Potterat et al, 2002;Gisselquist et al, 2003;Brewer et al 2003;Brody, 2004;Deuchert andBrody 2006, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…WHO studies showed that up to 5% of all HIV infections in Africa are due to unsafe injections including exposure to sharp injuries during unsafe handling of medical wastes [29,30]. On the other hand, data from two decades' studies in Africa estimated that contaminated needles and syringes used for medical treatments led to 48% of the HIV infections and sexual transmission though unprotected sex causes only 30% of the infections [31]. Study in Hawassa city of south Ethiopia showed that MCWs had experienced needle-stick injuries at least once in their life at the different HCFs ranged from 25-100% [15].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is important because, although an injection history was not reported, the seroconversions would not have occurred as a result of injections being given for treatment of an STI, as has been argued. 3 …”
Section: Sex As Primary Mode Of Hiv-1 Transmissionmentioning
confidence: 99%